Travestis envelhecem? - Antunes, Pedro Paulo Sammarco (2010)
This study is aimed to understand transgender aging context in Brazil. Aging and transgender are definitions that were created by society to organize its process of functioning. Biological sciences played a very important role concerning those definitions. They created what we call normal and abnormal. Our intention comprehends in getting to know what happens to those who are considered abnormal on gender rules. Because there is almost no study considering what is called transgender aging, this work is socially relevant. Gender and aging are understood to be natural and essential processes. However, they are performed by repeated actions that make us feel that gender and aging are inherent and happens exact the same way to everyone. For being considered deviants, transgender people are not seen as human beings. They end up living in violent environments. Their life expectancy is low. Many of them do not believe to reach old age. They face a lot of prejudice and death threat. Those who get to what we call old age are considered survivals. They become a model to the younger ones of their social group. This research was able to show satisfactorily their demands and needs. To be considered visible, they have to count on public policies to give them existence since their childhood. That way, we believe they will reach what we call old age with respect as dignity, already assured by the Universal Human Rights